Diaquabis(4-bromobenzoato-κO)bis(N,N′-diethylnicotinamide-κN1)zinc(II) - Hacali Necefoğlu; Fureya Elif Özbek; Tuncer Hökelek; Aslı Öztürk (Acta Crystallographica Section E, 2008)
The title compound, [Zn(C7H4BrO2)2(C10H14N2O)2(H2O)2], is a monomeric complex with the ZnII atom lying on an inversion center. It contains two 4-bromobenzoate, two diethylnicotinamide ligands and two water molecules, all of which are monodentate. The four O atoms in the equatorial plane around the Zn atom form a slightly distorted square-planar arrangement, while the distorted octahedral geometry is completed by two N atoms in the axial positions. The methyl group of one of the ethyl groups is disordered over two positions, with occupancies of ca 0.65 and 0.35. The two aromatic rings are oriented at an angle of 77.22 (14)°. In the crystal structure, O—H...O hydrogen bonds link the molecules into chains along the a axis.